The development of mural art in Kosovo 2020-2022 - Basha, Kosovar Kosovar (Street Art & Urban Creativity, 2023)
This paper shows the graffiti art in Kosovo during the time period 2020-2022. The presented murals unfold the Kosovar and foreign artists’ work in the cities of Kosovo, such as Prishtina and Ferizaj. The presented themes are of various different types in terms of their content. The graffiti works of foreign artists who exhibited their creative work at Mural Fest-Kosova in the above-mentioned years have given me a great help in developing this study. The author has carefully analyzed these graffiti and put them as they are, showing the contribution of graphic artists to contemporary art in Kosovo and beyond.